2012
DOI: 10.1074/jbc.m111.328237
|View full text |Cite
|
Sign up to set email alerts
|

Amidoxime Reductase System Containing Cytochrome b5 Type B (CYB5B) and MOSC2 Is of Importance for Lipid Synthesis in Adipocyte Mitochondria

Abstract: Background: High amidoxime reductase activity is found in liver and fat tissue, although its composition in cells is unknown. Results: Amidoxime reductase is up-regulated during adipogenesis and requires MOSC2 and CYB5B. Conclusion: MOSC2 and CYB5B are essential components of the mitochondrial amidoxime reductase, and MOSC2 is important for lipogenesis. Significance: We suggest a role of MOSC2 in adipogenesis and fatty acid synthesis and as a potential novel drug target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 40 publications
5
79
2
1
Order By: Relevance
“…Assuming a similar localization of mARC1 and mARC2, our results are in line with the previous studies detecting mARC2 in purified outer membrane fractions (5,9). In addition, for the first time we were also able to clarify the orientation of one of both mARC proteins in the outer membrane, demonstrating the exposure of the C-terminal catalytic domain toward the cytosol.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Assuming a similar localization of mARC1 and mARC2, our results are in line with the previous studies detecting mARC2 in purified outer membrane fractions (5,9). In addition, for the first time we were also able to clarify the orientation of one of both mARC proteins in the outer membrane, demonstrating the exposure of the C-terminal catalytic domain toward the cytosol.…”
Section: Discussionsupporting
confidence: 91%
“…Different views on the subcellular localization of mARC1 have been reported, localizing mARC1 to the outer or inner membrane of mitochondria (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in tissues of different species showed that at least one isoform of mARC was detectable in mitochondria (Da Cruz et al, 2003;Havemeyer et al, 2006;Wahl et al, 2010;Havemeyer et al, 2011;Krompholz et al, 2012;Neve et al, 2012). mARC-2 is also localized in peroxisomes (Islinger et al, 2007;Wiese et al, 2007).…”
Section: Introductionmentioning
confidence: 98%